Kontroversi Perkawinan Beda Agama di Indonesia - Sri Wahyuni (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2011)
This article discusses law problem of marriage between different religions in Indonesia, especially after the application of Bill number 1 year 1974 about marriage. In this discussion, the marriage between different religions is difficult to be done after the application of that Bill. Because of inadequate explanation about different‐religion marriage on the bill, there occurs problems on the interpretation and application. Referring to the Bill of Marriage Chapter 2, it is stated that it is not allowed to marry a person with different religion. However, based on Bill of Marriage number 66, the law expert stated that there is a vacant in that law, thus the rules of different‐religion marriage can be applied. In that way, the marriage between different religions can be done in the register office. On the reality, people of Indonesia still demand the application of marriage between different religions. That conclusion is gathered from the many marriages between different religions which relatively difficult to be done. For that reason, that problem needs to get solution.